Increased Striatal Injury and Behavioral Deficits after Intracerebral Hemorrhage in Hemopexin Knockout Mice - Chen, Lifen (2010)
OBJECT: Heme toxicity may contribute to the pathogenesis of intracerebral hemorrhage. The primary defense against extracellular heme is provided by hemopexin, a serum and neuronal glycoprotein that binds it with very high affinity and mitigates its pro-oxidant effect. In the present study, we tested the hypothesis that hemopexin knockout mice would sustain more injury after experimental intracerebral hemorrhage than their wild-type counterparts. METHODS: Striatal intracerebral hemorrhage was induced by stereotactic injection of bacterial collagenase or autologous blood. Three days later, striatal protein oxidation was assessed by carbonyl assay. Cell viability was quantified at 8-9 days using the methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay. Behavioral deficits were detected by high resolution digital analysis of six hour home cage video recordings and standard testing. RESULTS: Perihematomal protein oxidation was increased in wild-type collagenase-injected striata by approximately 2.1-fold compared with contralateral striata vs. 3-fold in knockouts. Striatal cell viability was reduced in wild-type mice to 52.9±6.5% of that in contralateral striata by collagenase injection, and to 31.1%±3.7% in knockouts; similar results were obtained after blood injection. Digital analysis of home cage video recordings demonstrated an activity deficit in both models that was significantly exacerbated at 8 days in knockouts. Striatal heme content 9 days after blood injection was increased approximately 2.7-fold by hemopexin knockout. CONCLUSION: These results suggest that hemopexin has a protective effect against hemorrhagic CNS injuries. Hemopexin deficiency, which is often associated with sickle cell disease, may worsen outcome after intracerebral hemorrhage.